2021
DOI: 10.5604/01.3001.0014.8759
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiotherapy on the quality of life in patients with early-stage clinical head and neck cancer

Abstract: Radiotherapy (RT) for patients with head and neck squamous cell carcinoma (HNSCC) affects vital functions related to the irradiation volume of the head and neck region and, in addition, has a negative impact on social functioning, thereby significantly impairing patients’ quality of life (QoL). The aim of this study was to assess changes in the quality of life in patients with head and neck cancer treated with curative RT at 12 months after completion of RT. The aim of this study was to assess the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In terms of the QLQ-H&N35 questionnaire, the authors reported a statistically significant deterioration in the QoL for scales of “dry mouth”, “weight loss”, “senses” “sticky saliva”, “opening mouth”, and “painkillers”. The effect of tumour location on QoL deterioration was statistically significant on the scales “speech” (higher deterioration in patients whose tumour was located in the larynx and hypopharynx) and “opening mouth” (higher deterioration when tumour was located in the oral cavity) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the QLQ-H&N35 questionnaire, the authors reported a statistically significant deterioration in the QoL for scales of “dry mouth”, “weight loss”, “senses” “sticky saliva”, “opening mouth”, and “painkillers”. The effect of tumour location on QoL deterioration was statistically significant on the scales “speech” (higher deterioration in patients whose tumour was located in the larynx and hypopharynx) and “opening mouth” (higher deterioration when tumour was located in the oral cavity) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is the most common reason for patients with HNC to leave their work [11,14], and it is more likely to appear with multimodality therapy than with single-modality therapy [4]. Moreover, dysphasia is often reported as a side effect of radiotherapy [31,32], one of the common reasons for quitting working after treatment [4] and signi cantly decreased HRQOL [26,33]. Thus, patients who were able to work might not receive adjuvant therapy and had fewer symptoms that would be a barrier to work.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advanced treatment methods in RT, the QOL is negatively impacted by HNC, even at early clinical stages [ 6 ]. QOL is important for HNC survivors and today as a study endpoint it is increasingly considered [ 7 ].…”
Section: Introductionmentioning
confidence: 99%